De la théorie à la pratique de la séquence Éviter-Réduire-Compenser (ERC) : éviter ou légitimer la perte de biodiversité ? - Charlotte Bigard; Baptiste Regnery; Sylvain Pioch; John D. Thompson (Développement Durable et Territoires)
The mitigation hierarchy has become a major regulatory tool to balance urban development with environmental interest. Notably, the success of its implementation is based on the interpretation of such politics by practitioners. In this manuscript, we focus on the interpretation of French normative definitions of the three steps in the mitigation hierarchy : i.e. avoidance, reduction et offsetting. The analysis of 42 Environmental Impact Assessment (EIA) highlights important heterogeneity among interpretations : 60 % of the proposed measures in EIAs do not fit with the normative definitions. These confusions could have a negative impact on the ecological efficiency of the mitigation hierarchy. Therefore, we suggest several solutions to improve cohesion between the normative definitions et proposed measures in practice.